2022
DOI: 10.1039/d2ob01709a
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur–DMSO promoted oxidative coupling of active methylhetarenes with amines: access to amides

Abstract: Elemental sulfur-DMSO couple was found to efficiently promote oxidative coupling of active methylhetarenes with amines to yield amides under simple heating conditions. When 2-methylquinoline was used as methylhetarene component, the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Therefore, the reaction conditions were slightly reoptimized with reference to the use of anilines and benzylamines to enhance the product yield, which disclosed a 1:1.5 molar ratio of 1 and 2 for 24 h as being ideal for the formation of the desired products 3p – 3z in good yields. However, the reaction of cinnamic acid with benzylamine invariably offered the anticipated product 3 along with the benzylamine homocoupled product amide/thioamide . The reaction of cinnamic acid with cyclohexylamine also afforded product 3z in 62% yield under the established conditions.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Therefore, the reaction conditions were slightly reoptimized with reference to the use of anilines and benzylamines to enhance the product yield, which disclosed a 1:1.5 molar ratio of 1 and 2 for 24 h as being ideal for the formation of the desired products 3p – 3z in good yields. However, the reaction of cinnamic acid with benzylamine invariably offered the anticipated product 3 along with the benzylamine homocoupled product amide/thioamide . The reaction of cinnamic acid with cyclohexylamine also afforded product 3z in 62% yield under the established conditions.…”
Section: Resultsmentioning
confidence: 95%
“…However, the use of external H 2 O (1–3 equiv) in DMSO reduced the yield of the desired product considerably (Scheme , eq d). On the basis of these two control experiments, we concluded that the H 2 O as such has no positive role in the reaction and, instead, DMSO plays the key role as an oxidant for the conversion of thioamide to amide …”
Section: Resultsmentioning
confidence: 99%
“…1 Consequently, the synthesis of pyridine carboxamides has always been the focus of organic chemists. 2–6 Traditionally, pyridine carboxamides were synthesized from pyridine carboxylic acids and their activated derivatives using amines with a high step economy. 2 However, excess amounts of expensive dehydrating or unstable preactivation agents were required, resulting in tedious synthetic operation, low yields and so on.…”
mentioning
confidence: 99%
“…Later, several improved protocols were developed via oxidative amidation of aldehydes 3 or methylarenes. 4 To some extent, high temperature and chemical oxidants restricted these methods. Very recently, Laha reported the synthesis of pyridine carboxamides via a TBHP-mediated denitrogenative strategy (Scheme 1a).…”
mentioning
confidence: 99%
“…The optimal Ni(OAc) 2 ·4H 2 O catalyst loading turned out to be 15 mol % (entries 13–16), where the formation of product 4a peaked at 92% yield (entry 14). The control experiments also confirmed the possible use of another nickel catalyst NiCl 2 ·6H 2 O (entry 18), the importance of NEt 3 (entry 19), and the defined catalyst role of nickel in the [3 + 2] cycloaddition reaction (entry 20).…”
mentioning
confidence: 99%